Implementation of Experiments in Science Learning in the Form of Rhoeo discolor Plasmolysis Practicum - Dina Fatin Nafisah; Sofiatun (Journal of Progressive Science Education, 2025)
Plasmolysis experiments on plant tissues were carried out to find out and explain changes in Rhoeo discolor epidermal cells before and after plasmolysis, as well as to analyze the factors that cause plasmolysis. Plasmolysis experiments on plant tissues use data collection methods or techniques in the form of experiments or experiments and documentation. The results of the plasmolysis experiment on plant tissue are that before plasmolysis occurs, the cell wall is tight and the color of the cell is deep purple. After plasmolysis, the cell wall will stretch with a faded purple color. The results of the experiment obtained are in accordance with the hypothesis that has been presented and show that this practicum is in accordance with the theory. The data produced is in the form of statements or sentences so that this experiment is a type of qualitative research. Changes in the shape of the cell wall and the color of the cell are caused by the presence of a NaCl solution that is concentrated higher than the concentration of water in the cell. The difference in concentration causes excessive transfer of substances which causes plasmolysis in the epidermal cells of Rhoeo discolor. The results of this experiment are useful to be applied in learning and become a learning resource for junior high school students in grade VIII. This experimental method also trains critical thinking and improves students' critical thinking skills.